Functional Balance Assessment: review - Alonso,Angélica Castilho (2014)
The aim of this study was to perform a literature review on different methods of postural balance assessment and to provide a theoretical framework for further study of this subject. Medline, PubMed and LILACS databases were used to find currently employed methods which show good reproducibility and reliability. Clinical examination and scale application or force platform testing, each one with their own advantages and limitations, can be used to assess postural balance. There is no common standard. The evaluator should be familiar with all available methods in order to be able to select the most appropriate for his specific requirements.